Additions to the genus Corynespora from India - and P. MEHTA, SEEMA LATA JAIN, AN. RAI* (Indian Phytopathology, 2012)
Studies of phytoparasitic fungi of forests and cultivated plants of Madhya Pradesh, revealed many leaf spot collections. Detailed morphotaxonomic investigations of some of them revealed three hitherto undescribed species of Corynespora viz., C. bombacearum on Bombax malabaricum DC. (Bombaceae), C. holopetae on Holoptelea integrifolia Linn. (Ulmaceae) and C. zizyphae on Zizyphus grialdii (Rhamnaceae). These are described, illustrated and compared with allied species.